1996
DOI: 10.2105/ajph.86.2.231
|View full text |Cite
|
Sign up to set email alerts
|

Smoking prevalence in US birth cohorts: the influence of gender and education.

Abstract: OBJECTIVES. To assess long-term trends in cigarette smoking according to the combined influence of sex and education, this study examined smoking prevalence in successive US birth cohorts. METHODS. Data from nationally representative surveys were examined to assess smoking prevalence for six successive 10-year birth cohorts stratified by race or ethnicity, sex, and educational attainment. RESULTS. Substantial declines in smoking prevalence were found among men who had a high school education or more, regardles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
146
1
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(168 citation statements)
references
References 25 publications
17
146
1
2
Order By: Relevance
“…Nevertheless, some selection bias is inevitable, as reflected in the data on current smoking in table 5. These rates are lower by 30-50 percent when compared with corresponding data from national surveys (21). Thus, we can expect a lower incidence of lung and other smoking-related cancers in the cohort compared with the general population of Hawaii and California.…”
Section: Commentmentioning
confidence: 67%
“…Nevertheless, some selection bias is inevitable, as reflected in the data on current smoking in table 5. These rates are lower by 30-50 percent when compared with corresponding data from national surveys (21). Thus, we can expect a lower incidence of lung and other smoking-related cancers in the cohort compared with the general population of Hawaii and California.…”
Section: Commentmentioning
confidence: 67%
“…First, it was performed in men only. Thus, it may not be appropriate to extrapolate the results to women, given the gender differences in the prevalence and characteristics of smoking habits (Escobedo and Peddicord, 1996;Hill, 1998;Osler et al, 1999;Dedobbeleer et al, 2004). Indeed, studies in Japan have reported more pronounced associations between F&V intake and CVD in men than in women (Nakamura et al, 2008;Takachi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Even though smoking has decreased among all socio-economic groups, some studies have found that differences between groups have remained stable or even increased over time (Escobedo and Peddicord, 1996;Giskes et al, 2005;Peretti-Watel et al, 2009), which suggest that that diffusion has been blocked or delayed. Following this line of thought, Dixon and Banwell argued that the smoking epidemic model should include a fifth stage marked by "sedimentation of smoking in successive low SES cohorts" (Dixon and Banwell, 2009). 3.…”
Section: Diffusion Of Cigarette Smoking Behaviormentioning
confidence: 99%